Comparative Analysis of Mortality Rates and Whole Life Insurance Premiums Based on the Indonesian Mortality Table IV (TMI IV) - Banjarnahor, Riski; Lumbantobing, Imelda Octavia; Sianturi, Michael Dolly (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Universitas Pamulang, Indonesia, 2026)
This study aims to analyze the comparative mortality rates and whole life insurance premiums between males and females based on the Indonesian Mortality Table IV (TMI IV), as well as to examine the phenomenon of risk convergence at older ages and the implications of interest rates on premium sensitivity. This study employs a quantitative approach using actuarial simulation methods. The data used are secondary data from TMI IV published by the Indonesian Life Insurance Association (AAJI) for the study period of 2013–2017. The net annual premium is calculated using the commutation function (Pₓ = Mₓ / Nₓ), assuming a sum assured of IDR 100,000,000 and a technical interest rate of 6%. The results indicate that male mortality rates are higher than those of females across productive ages to early elderly stages, as reflected in the female survival curve being consistently above that of males. At age 80, out of an initial cohort of 100,000 individuals, 62,171 males (62.2%) remain, compared to 70,207 females (70.2%). The annual premiums for whole life insurance are higher for males than for females across all age groups, with premium differences ranging from 19.3% to 27.2%. The phenomenon of mortality convergence is observed through the narrowing premium gap between genders as age increases. Sensitivity analysis shows that premiums have an inverse relationship with interest rates, where a 1% decrease in the technical interest rate can increase premiums by approximately 8–12%. This study concludes that TMI IV effectively represents current mortality dynamics in Indonesia and serves as a crucial foundation for actuarial liability calculations, while age and interest rates significantly influence the determination of whole life insurance premiums.